A review of agriculture and health policies in Uganda with implications for the dissemination of biofortified crops - Potts, Michael J.; Nagujja, Stella (International Food Policy Research Institute, 2007)
Micronutrient deficiency is a widespread health problem in the developing world. Most efforts to combat this issue have focused on providing vitamin and mineral supplements to vulnerable population groups and/or fortifying foods through postproduction processing. The outcome of these interventions has not always been successful; particularly as isolated communities are often not reached due to logistical problems or do not regularly consume processed products. Also, supplementation interventions are frequently dependent on external funding and thus their sustainability is questionable.